2020
DOI: 10.9787/kjbs.2020.52.s.179
|View full text |Cite
|
Sign up to set email alerts
|

60 Years of Forest Tree Improvement in Korea : Accomplishments and Prospects

Abstract: Forest tree improvement is relatively a young science and its purpose is to provide guidance for the conservation, management and sustainable utilization of genetic resources of natural and managed forests. In South Korea, forest tree improvement programs started in 1956. The programs had two main aims: to guarantee the genetic origin of the forest reproductive materials used in afforestation and reforestation, and to develop genetically improved individuals and varieties of some commercially important trees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Kyoukyul refers to "the strong socio-psychological motivation of Korean parents to educate their children" (J Lee, 2010, p. 362). The unique education institution and culture of Korea resulted in Kyoyukyul (J Lee, 2010;Oh, 2015). First, the open school system and the way to select students, irrespective of their socio-economic status, prompted parents to invest heavily into education.…”
Section: Education Fever Vs Humanitarian Discoursesmentioning
confidence: 99%
“…Kyoukyul refers to "the strong socio-psychological motivation of Korean parents to educate their children" (J Lee, 2010, p. 362). The unique education institution and culture of Korea resulted in Kyoyukyul (J Lee, 2010;Oh, 2015). First, the open school system and the way to select students, irrespective of their socio-economic status, prompted parents to invest heavily into education.…”
Section: Education Fever Vs Humanitarian Discoursesmentioning
confidence: 99%
“…The measurement tool was a quiz related to the content of the class; all self-produced tools were used. The measurement of the results of the cognitive domain according to the intervention was assessed immediately after class (16) and after delay (4); in total, 20 tests had been administered. Among them, nine studies reported that they were effective as a result of testing the cognitive knowledge immediately after class [33][34][35][36][37][38][39]42,43], and four studies [23,37,40], reported that they were effective after class.…”
Section: Cognitive Domainmentioning
confidence: 99%
“…Additionally, everyday access to forest education might have practical difficulties caused by weather and seasonal restrictions. When analyzing the use status and demand for forest education among adults, "accessibility" was selected as the most important consideration for all age groups when selecting forest education (42.1%) [16]. In addition, "lack of access to public transportation" was cited as the top inconvenience that hinders participation in forest education for all ages [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation